2021
DOI: 10.3390/molecules26113081
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Medicinal Plants and Bioactive Natural Compounds on Homocysteine

Abstract: Background: Among non-communicable diseases, cardiovascular diseases (CVDs) are the leading cause of mortality and morbidity in global communities. By 2030, CVD-related deaths are projected to reach a global rise of 25 million. Obesity, smoking, alcohol, hyperlipidemia, hypertension, and hyperhomocysteinemia are several known risk factors for CVDs. Elevated homocysteine is tightly related to CVDs through multiple mechanisms, including inflammation of the vascular endothelium. The strategies for appropriate man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 229 publications
(236 reference statements)
1
9
0
Order By: Relevance
“…This may explain why there was no difference in the expression of NOX2 and NOX4 proteins between the HHCY + RSV and HHCY + FA groups. Furthermore, the results of the present study demonstrated that RSV reduced the serum HCY levels, which is consistent with previous research (16). However, this change was not as significant as for FA treatment, as there was no significant difference between FA and RSV in terms of improving renal function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This may explain why there was no difference in the expression of NOX2 and NOX4 proteins between the HHCY + RSV and HHCY + FA groups. Furthermore, the results of the present study demonstrated that RSV reduced the serum HCY levels, which is consistent with previous research (16). However, this change was not as significant as for FA treatment, as there was no significant difference between FA and RSV in terms of improving renal function.…”
Section: Discussionsupporting
confidence: 92%
“…The natural antioxidant RSV improves diabetic kidney damage and delays kidney aging (23,24). Moreover, it has previously been confirmed that RSV can reduce HCY levels (16). Therefore, RSV may be a potential treatment for HHCY-induced hypertensive renal damage.…”
Section: Discussionmentioning
confidence: 92%
“…Mollisto treats the renal injury induced by ischemia-reperfusion. Another study conducted on walnuts confirmed that the hepatoprotective impact of the walnut extract was beneficial against liver damage caused by CCl4 in rats 24 .…”
Section: Discussionmentioning
confidence: 87%
“…Throughout these services, plants have a positive influence on the human population and mostly on human wellbeing [ 2 , 3 , 4 ]. As a consequence, recent decades have witnessed a continuous interest of the scientific field towards medicinal plants, natural products [ 5 , 6 , 7 ] and apitherapy [ 8 , 9 ] that can provide important resources for sustainable development [ 10 , 11 ]. Because of the importance given to plants for preventing and curing various diseases, their role has grown, and more attention has been given to the secondary metabolites and their nutritional and health benefits [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%